THE STUDY OF INFLUENZA VIRUS NEURAMINIDASE HYDRATION DEGREE - N. S. Grebenkina (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
It is known that the functioning of many proteins and enzymes depends on the degree of hydration of their surfaces. In our studies, neuraminidase (NA) of influenza virus was selected as a model for surface antigenic viral protein. The Brunauer–Emmett–Teller (BET) model of adsorption was used to calculate the values of water monolayer (am) at different values of water vapor pressure. The obtained BET isotherms allow for concluding that hysteresis takes place manifested by the difference between the monolayer am values for sorption and desorption of water from the surface of the enzyme, which is probably associated with a high degree of cooperation of the hydration shell formed. The maximum binding of water molecules was observed for the vapor pressure p/ps value of 0.65 and was am = 224 water molecules per a molecule of the enzyme. Basing on the calculated surface area of a NA tetramer (S = 256 nm2 ) and the maximum projection area of water molecule, it may be concluded that the entire surface of the enzyme is completely covered with a water monolayer. For said am value the maximum activity of NA was observed, whereas the minimum enzyme activity corresponded to the am value of 98 water molecules per a molecule of the enzyme, which corresponded to the water vapor pressure p/pS value of 0.38. Thus, for the influenza virus NA protein a dependency of the enzymatic activity on the degree of hydration of the surface of the enzyme is demonstrated. The dependence of immunogenicity of influenza virus from the extent of hydration of NA.